Forest Herbicide Characteristics - Anna Osiecka; Patrick J. Minogue (EDIS, 2011)
The effectiveness and safe use of herbicides registered for forest vegetation management in Florida requires developing site-specific herbicide prescriptions made with careful consideration of site factors and knowledge of the chemical and physical properties of herbicides and their effects on biological systems. This 9-page fact sheet was written by Anna Osiecka and Patrick J. Minogue, and published by the UF Department of School of Forest Resources and Conservation, May 2011.